1992
DOI: 10.1007/bf01250670
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic unpredictable stress on locomotor and exploratory activity in male rats with different endogenous prolactin levels

Abstract: The probable role of prolactin (PRL) on the behavioral responses evoked by chronic unpredictable stress (CUS) was studied in adult male rats. Three experiments were performed examining the effect of CUS on behavioral performance in: (i) intact rats with normal endogenous PRL levels, (ii) rats with high endogenous PRL levels, and (iii) rats with low endogenous PRL levels. Behavioral parameters studied were: locomotion, head-dipping, rearing and grooming. Endocrine parameters studied were: PRL and corticosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Under strong stressful conditions, PRL increases locomotor activity and present results are in agreement with that found by Drago etal. (1982) and Fracchia et al (1992), who found in different experimental models an augmented motor activity associated with high endogenous PRL levels. The present data tell virtually nothing about the mechanisms of action of PRL in the HPC cells.…”
Section: Methodsmentioning
confidence: 96%
“…Under strong stressful conditions, PRL increases locomotor activity and present results are in agreement with that found by Drago etal. (1982) and Fracchia et al (1992), who found in different experimental models an augmented motor activity associated with high endogenous PRL levels. The present data tell virtually nothing about the mechanisms of action of PRL in the HPC cells.…”
Section: Methodsmentioning
confidence: 96%
“…The falling P4 levels, rather than the absolute concentration of the steroid, can lead to significant changes in the excitability of GABA-containing circuits (see Lovick, 2006). PRL is another putative hormone that may cause the lower scores of anxiety observed at P, since a peak of PRL is observed at this stage (Furudate et al, 1989) and the anti-stress properties of PRL have been well documented (see Fracchia et al, 1992;Torner et al, 2001;Torner, Toschi, Neva, Clapp, & Neumann, 2002;Donner & Handa, 2009).…”
Section: Proestrusmentioning
confidence: 99%